Use Activated Carbon Prepared from Some Palm Waste to Remove Co(II) and Cu(II) from Sewage Water - Firas Ali Hussein Alhameedawi; Mohammed Khlaif Challab; Mohammed Turki Khathi (University of Thi-Qar Journal of Science, 2020)
This study included the use of palm waste such as fiber and tree leaves palm, as low cost adsorbents for removal of Cu(II) and Co(II) from sewage water via preparation of activated carbon. The results are showed that the adsorption equilibrium time was 35 and 45 min for both metals by tree leaves and fiber respectively. The obtained results indicated that over pH (6.5) there is an increased optimum of adsorption for both metal ions. The study showed that (0.4 g) of adsorbent is very ideal to obtain the best adsorption for both studied ions. The capacity of the adsorbents Co(II) to adsorb high than Cu(II).